Formation of the Main Areas of the Economy Prosperity and Living Standards - Томчук-Понамаренко, Н. (Київський національний університет імені Тараса Шевченка, 2014)
У статті здійснено аналіз еволюції наукових поглядів на сутність категорії "рівень життя населення" та деяких методичних аспектів її дослідження. Визначено основні наукові напрями економіки добробуту в історії досліджень життєвого рівня населення. Запропоновані характеристики, що мають вплив на вивчення та оцінку рівня життя населення.

Social-economic essence of the category of "social standard of living" is disclosed, and its correlation with the other synonymic categories such as "human wellbeing", "living conditions", "social standard of living", "quality of life" and "mode of life" is shown. Evolution of scientific views on the essence of the category of social standard of living as well as some methodical aspects of its study is put under analysis. Main directions of welfare economics are described in history of researches of standard life of population in world practice. Parameters relevant to social standard of living's study and assessment are suggested
Формування основних напрямів економіки добробуту та рівня життя населення
Keywords: рівень життя населення; якість життя; добробут; соціальна нерівність; social standard of living; quality of life; well-being; social inequality